Proarrhythmic safety of repeat doses of mirabegron in healthy subjects: a randomized, double-blind, placebo-, and active-controlled thorough QT study - Malik, M; van Gelderen, E M; Lee, J H; Kowalski, D L; Yen, M; Goldwater, R; Mujais, S K; Schaddelee, M P; de Koning, P; Kaibara, A; Moy, S S; Keirns, J J (Clinical pharmacology and therapeutics, 2012)
Potential effects of the selective β(3)-adrenoceptor agonist mirabegron on cardiac repolarization were studied in healthy subjects. The four-arm, parallel, two-way crossover study was double-blind and placebo- and active (moxifloxacin)-controlled. After 2 baseline ECG days, subjects were randomized to one of eight treatment sequences (22 females and 22 males per sequence) of placebo crossed over with once-daily (10 days) 50, 100, or 200 mg mirabegron or a single 400-mg moxifloxacin dose on day 10. In each period, continuous ECGs were recorded at two baselines and on the last drug administration day. The lower one-sided 95% confidence interval for moxifloxacin effect on QTcI was >5 ms, demonstrating assay sensitivity. According to ICH E14 criteria, mirabegron did not cause QTcI prolongation at the 50-mg therapeutic and 100-mg supratherapeutic doses in either sex. Mirabegron prolonged QTcI interval at the 200-mg supratherapeutic dose (upper one-sided 95% CI >10 ms) in females, but not in males.